Electron pitch angle distribution during magnetic reconnection diffusion region observations in the Earth's magnetotail - A. L. Borg; M. G. G. T. Taylor; J. P. Eastwood (Annales Geophysicae, 2012)
The Earth's magnetosphere provides an excellent laboratory for magnetic reconnection research. In particular, the magnetotail current sheet that is formed between the interface of the similar Northern and Southern Hemispheres of the magnetotail provides a relatively stable symmetric reconnection configuration that can be used to study basic aspects of the reconnection process. Of particular importance is the manner in which electrons are processed by the reconnection. Simulations and satellite data analyses of the ion diffusion region have suggested that the fluxes of electrons in the inflow regions of reconnection are greater in the directions parallel and anti-parallel to the magnetic field (field-aligned) whereas the electron flux in the outflow region is distributed more isotropically. However, this has only been studied experimentally on a case-by-case basis. In this paper, we investigate this claim by analyzing the degree of bulk electron field alignment in the outflow and inflow regions during encounters of the magnetic reconnection ion diffusion region by the Cluster spacecraft in the years 2001–2006. We demonstrate that while the median electron flux in the inflow region is indeed more field aligned than in the outflow region during some ion diffusion region encounters, the variation of the signature across events is so large that it cannot be said to be a general feature of magnetic reconnection in the Earth's magnetotail.